Kajian Ulang Muthlak dan Muqayyad Sebagai Metode Istinbat Hukum - Helvia Putri; Elsa Elvionita; Silvi Sri Insani; Weldra Ayu Putri; Muchlis Bahar; Firdaus Firdaus (Mathematics Education Study Program, 2025)
This paper examines the concepts of muthlaq and muqayyad within the context of Islamic law, employing the Mutakallimin and Hanafiyah methods. These two concepts are crucial in understanding and interpreting legal texts in the Quran and Sunnah. Muthlaq refers to an unbound or unrestricted term, while muqayyad refers to a term that has been restricted by another term. This research uses a literature review method to analyze the definitions, examples, and applications of the concepts of muthlaq and muqayyad. The differences between the Mutakallimin and Hanafiyah methods in interpreting these two concepts are also discussed and compared.